Cognitive Dysfunction in Repeat Expansion Diseases: A Review - Zhang, Sizhe; Shen, Lu; Jiao, Bin (Frontiers in Aging Neuroscience, 2022)
With the development of the sequencing technique, more than 40 repeat expansion diseases (REDs) have been identified during the past two decades. Moreover, the clinical features of these diseases show some commonality, and the nervous system, especially the cognitive function was affected in part by these diseases. However, the specific cognitive domains impaired in different diseases were inconsistent. Here, we survey literature on the cognitive consequences of the following disorders presenting cognitive dysfunction and summarizing the pathogenic genes, epidemiology, and different domains affected by these diseases. We found that the cognitive domains affected in neuronal intranuclear inclusion disease (NIID) were widespread including the executive function, memory, information processing speed, attention, visuospatial function, and language. Patients with C9ORF72-frontotemporal dementia (FTD) showed impairment in executive function, memory, language, and visuospatial function. While in Huntington's disease (HD), the executive function, memory, and information processing speed were affected, in the fragile X-associated tremor/ataxia syndrome (FXTAS), executive function, memory, information processing speed, and attention were impaired. Moreover, the spinocerebellar ataxias showed broad damage in almost all the cognitive domains except for the relatively intact language ability. Some other diseases with relatively rare clinical data also indicated cognitive dysfunction, such as myotonic dystrophy type 1 (DM1), progressive myoclonus epilepsy (PME), Friedreich ataxia (FRDA), Huntington disease like-2 (HDL2), and cerebellar ataxia, neuropathy, vestibular areflexia syndrome (CANVAS). We drew a cognitive function landscape of the related REDs that might provide an aspect for differential diagnosis through cognitive domains and effective non-specific interventions for these diseases.